Pengembangan Bahan Ajar IPA Berbasis Inkuiri Terbimbing untuk Meningkatkan Literasi Sains - Baiq Sri Komalasari; A Wahab Jufri; Didik Santoso (Postgraduate, University of Mataram, 2019)
Abstract: The purpose of this study is to produce a product in the form of science teaching materials that can improve the scientific literacy of students. This research is included in research and development of education which is a method for producing certain products and testing the effectiveness of these products. The product developed was validated by experts consisting of 3 people. Learning tools that are validated are syllabus, lesson plans, and scientific literacy instruments. The results of the study show that the learning device in the form of syllabus shows an average of 3.9 (78%) in the appropriate category, the Learning Implementation Plan (RPP) shows an average of 3.9 (78%) in the feasible category, and the items show the average value is 4.1 (82%) in the feasible category. Thus, inquiry-based science teaching materials developed in appropriate categories can be applied in learning. The results of the questionnaire response analysis of students showed that students' responses were very good for teaching materials because 77.8% of students were fluent that guided inquiry-based teaching material was interesting. In a large-scale trial, the N-gain value obtained in the experimental class was 70.74 with high criteria. Keywords: Science Teaching Materials; Guided Inquiry; Science Literacy